2016
DOI: 10.1016/j.polymer.2016.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Processable conductive graphene/polyethylene nanocomposites: Effects of graphene dispersion and polyethylene blending with oxidized polyethylene on rheology and microstructure

Abstract: Poor dispersion of graphene in non-polar polymer matrices creates composites with limited applications. A method to improve the dispersion of graphene in polyethylene (PE) via blending PE with oxidized PE (OPE) is examined. Graphene was produced by simultaneous thermal exfoliation and reduction of graphite oxide. Nanocomposites of graphene with PE as well as graphene with PE/OPE-blends were prepared by solvent blending. Improved dispersion of graphene in PE/OPE blends substantially decreases percolation from b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 75 publications
3
55
0
3
Order By: Relevance
“…Polymer nanocomposites have shown enormous potential to significantly enhance the polymers properties by using nano‐scale fillers . Graphene has recently become one of the most promising nanofillers for polymer nanocomposites because of its extraordinary mechanical, thermal and electrical properties .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymer nanocomposites have shown enormous potential to significantly enhance the polymers properties by using nano‐scale fillers . Graphene has recently become one of the most promising nanofillers for polymer nanocomposites because of its extraordinary mechanical, thermal and electrical properties .…”
Section: Introductionmentioning
confidence: 99%
“…Graphene has recently become one of the most promising nanofillers for polymer nanocomposites because of its extraordinary mechanical, thermal and electrical properties . Graphene is a sp 2 ‐hybridized carbon layer with an atomic thickness, consisting of honeycomb‐like assembly of carbon atoms . This structure exhibits exceptionally high modulus (~1,000 GPa in tension), which can result in significant improvements in mechanical properties (over 100% increase in Young's modulus) when added to a polymer matrix .…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al [73] found that the π-π structured plane of humic acid (HA) can be absorbed on the surface of graphene, which supplied oxygen-containing groups to graphene sheets to improve the dispersion of graphene in water. Iqbal et al [74] proposed an approach to …”
Section: Using a π-π Interactionmentioning
confidence: 99%
“…Graphene has been known as promising adsorbent with great potential in wastewater treatment [5][6][7] because of its large theoretical surface area (2630 m 2 /g) [8], remarkable electronic properties [9] and mechanical properties [10], and high ability of modification [11,12]. However, it is difficult to disperse graphene in water due to its hydrophobicity, agglomeration, and restacking [13][14][15], limiting its use in aqueous systems for decontamination.…”
Section: Introductionmentioning
confidence: 99%